Inclusion of Special Education students in rural schools: possibilities for collaborative work? - Washington Cesar Shoiti Nozu; Mônica Aparecida Souza da Silva; Bruno Carvalho dos Santos; Eduardo Adão Ribeiro (Universidade Federal do Norte do Tocantins, 2020)
This article aimed to describe the contingency of the inclusion process in a rural school, with emphasis on the pedagogical work carried out by the regent and specialist teachers to meet the special educational needs of students with disabilities, global developmental disorders and high skills / giftedness - defined as Special Education Target Public (SETA). Methodologically, it followed the paths of collaborative research, with the setting of a school in the countryside of Mato Grosso do Sul and as participants three managers and 23 teachers from the teaching unit. For that, it made use of documentary analysis, observation, interviews and reflective sessions, whose data were systematized in two axes. The first contextualized the rural school, its structure and functioning, the number of general enrollments and SETA students and the Special Education services available. The second focused on the relationship between the regent teachers and the specialist teachers, as well as presenting the development of reflective sessions aimed at building collaborative work to enhance the inclusion of SETA students in rural schools. It's expected that the research-training contributes to articulations between the University and the School, as well as between ordinary and specialized education with a view to improving the schooling conditions of rural SETA students.